The effect of tax avoidance on profitability with corporate governance as moderation - Sunu, Gede Gangga Wiweka (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The increase in profitability in most companies listed on the Indonesia Stock Exchange occurred from 2017 to 2019. Consumer Non-cyclical sector companies began to show an increase in profitability from 2021 to 2022. The aim of this research is to analyze the effect of Tax Avoidance on Profitability with Corporate Governance as moderator. This research uses a quantitative descriptive method carried out on non-cyclical consumer companies listed on the Indonesia Stock Exchange for the 2020-2022 period. A total of 38 companies as samples in this research observed financial report data for 3 years, namely from 2020 to 2022 using the Moderated Regression Analysis (MRA) analysis model. The research results show that tax avoidance has no effect on profitability, corporate governance has a positive and significant effect on profitability, and corporate governance is unable to strengthen the effect of tax avoidance on profitability.